2014
DOI: 10.1063/1.4870803
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic strain, magnetic properties, and lattice dynamics in self-assembled multiferroic CoFe2O4-PbTiO3 nanostructures

Abstract: Articles you may be interested inAdjustable magnetoelectric effect of self-assembled vertical multiferroic nanocomposite films by the in-plane misfit strain and ferromagnetic volume fraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…We found that the values of t DL and M s are in good agreement with previous studies [10,[28][29][30] and strongly depend on the layering structure of the samples and the annealing procedure they have undergone. For the as grown structures, the magnetic dead layer is found to be extremely thin in the bottom Ta/CoFeB/MgO samples (t as grown DL,bottom = 0.04 nm), while the magnetic dead layer is thicker in the top MgO/CoFe-B/Ta samples (t as grown DL,top = 0.25 nm).…”
Section: Cofeb-mgo Filmssupporting
confidence: 91%
“…We found that the values of t DL and M s are in good agreement with previous studies [10,[28][29][30] and strongly depend on the layering structure of the samples and the annealing procedure they have undergone. For the as grown structures, the magnetic dead layer is found to be extremely thin in the bottom Ta/CoFeB/MgO samples (t as grown DL,bottom = 0.04 nm), while the magnetic dead layer is thicker in the top MgO/CoFe-B/Ta samples (t as grown DL,top = 0.25 nm).…”
Section: Cofeb-mgo Filmssupporting
confidence: 91%
“…For cubic CFO with the Fd 3m symmetry, the E g and pronounced A 1g modes are allowed at 300 cm À1 and 700 cm À1 , respectively, in the ZðXXÞ Z configuration. 7 According to the P 4mm symmetries for an a-domain oriented tetragonal BTO, the E(TO) modes are allowed in the ZðXYÞ Z geometry. 23,24 Since E(TO) mode appears at 310 cm À1 as shown in the inset of Fig.…”
Section: (B) and 3(c)mentioning
confidence: 99%
“…Multiferroic materials simultaneously displaying ferroelectric and ferromagnetic materials have attracted research interests for the coupling between magnetic and electric orders. 1 Recently, much effort has been carried out to realize the stress-mediated coupling in multiferroic materials by applying the external electric fields 2-5 or magnetic fields 6,7 to generate large strain for manipulating the magnetic (or ferroelectric) properties. Because ferroelectric materials undergoing the structural transitions at their Curie temperatures can produce large strain to rotate the magnetic domains, temperature could be a new parameter to modify the interfacial coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation